Dynamic performance for a kW-grade air-cooled proton exchange membrane fuel cell stack. (1st October 2022) - Zhu, Kai-Qi; Ding, Quan; Xu, Jiang-Hai; Yang, Chen; Zhang, Jing; Zhang, Yan; Huang, Tai-Ming; Wan, Zhong-Min; Wang, Xiao-Dong
Abstract: In this study, a kW-grade air-cooled proton exchange membrane fuel cell (PEMFC) stack with a dead-end anode (DEA) operation is designed and manufactured. The gravity-assisted drainage principle is applied for the stack to design the wettability of gas diffusion layers (GDLs) and the anode channel geometry, which can help the liquid water that diffuses to the anode to drain out of the anode porous electrode and move down the anode channel outlets. As a result, the stack can stably operate in a long purge interval of 268 s and in a short purge time of 2 s. In addition, using this design, only four small-power fans are employed to pump air to the cathode to provide oxygen for the electrochemical reaction and cool the stack. With a constant load current of 30, 45, or 60 A, the stack output voltage is experimentally tested at various cathode air flow rates (CAFRs). The local temperatures (60 measurement points) inside the stack and the pressure differences across anode channels are also monitored to understand heat dissipation and the back diffusion of liquid water. In a wide range of operating conditions, the designed stack possesses superior and stable voltage output characteristics with relatively uniform temperature distributions. The measured maximum output power is 3.83 kW, and the parasitic powers of fans are only 80∼112 W. Highlights: A kW-grade air-cooled PEMFC system under dead-ended anode operation is designed. The effect of cathode air flow rate on dynamic temperature evolution is studied. Modified anode channels based on gravity drainage are applied to the cell system. A stringing fan arrangement is used to improve cooling efficiency.